PTH-014 Does flexible sigmoidoscopy increase the polyp and cancer detection yield when used to supplement CT colonography?. (23rd September 2015) - Selinger, C P; Mullender, J; Choudhury, S; Jones, P E; Sukumar, S; Ramesh, J
Abstract : Introduction: Flexible sigmoidoscopy (FS) increases the polyp and carcinoma detection yield when used as an addition to double contrast Barium enema.1 The addition of FS to Barium enema has therefore been advised as standard practice.2 CT colonography (CTC) has replaced Barium enemas in many hospitals. We aim to explore whether FS increases the polyp and carcinoma detection yield when used as an addition to CTC. Methods: Using endoscopy and radiology databases patients who underwent both FS and CTC between 2007 and 2009 were identified. Data were collected from those databases and the electronic patient records. Analysis was based on performed tests regardless of quality of bowel prep (FS and CTC), ability to retain gas (FS and CTC) or extent of procedure (FS). Yields of polyp, adenoma and carcinoma detection were calculated. Serious pathology was defined as cancers and adenomas >9 mm. Results: A total of 294 patients (179 female; 60.8%), with a mean age of 67 years were included. CTC detected 36 patients with carcinomas while FS detected 26. One rectal cancer not seen on CTC was diagnosed by FS. Polyps were seen by CTC in 71 and by FS in 47 patients. In five patients FS found polyps that were not detected by CTC, 3 of which were small (5 mm) adenomas. FS detected extra adenomas or carcinomas in four of 294 cases, producing a yield of 1.36%. The number needed to endoscope to detect one extra adenoma was 74. Serious additional pathology was detected by FS in a single case, producing a yield of 0.34%. The number needed to endoscope to detect one extra serious pathological finding was 294. Conclusion: FS has a low yield of adenomas when used as an additive to CTC. The yield for serious pathology was very small in our series. Based on these findings the usefulness of routine use of FS as a supplement to CTC for adenoma and carcinoma detection is questionable. FS can however provide valuable additional information about inflammation, infection or vascular lesions depending on indication.